2020
DOI: 10.1007/s40544-020-0407-y
|View full text |Cite
|
Sign up to set email alerts
|

Rheological and tribological approaches as a tool for the development of sustainable lubricating greases based on nano-montmorillonite and castor oil

Abstract: This study investigates the development of novel montmorillonite/castor oil blends to formulate sustainable lubricating greases to promote the replacement of petrochemicals industry-derived materials by substances obtained from renewable sources. Specifically, the effect of the thickener concentration on the rheological, chemical, thermal, tribological properties, and atomic force microscopy (AFM) microstructure of these systems were studied. The results showed that the C20A nanoclay content could be used to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 30 publications
4
18
0
Order By: Relevance
“…As shown in Figure 3, the values of G' and G'' for the LS gels remained constant over a wide range of strain amplitudes, indicating that both of these gels had a relatively wide LVR. This viscoelastic behavior is similar to that previously reported for gel-like dispersions [28][29][30][31]. Compared with LS(0) gel, the storage modulus (G') of LS(0.20) gel was found to be about 8.2 times higher.…”
Section: Rheological Properties Of Ls Gelssupporting
confidence: 89%
“…As shown in Figure 3, the values of G' and G'' for the LS gels remained constant over a wide range of strain amplitudes, indicating that both of these gels had a relatively wide LVR. This viscoelastic behavior is similar to that previously reported for gel-like dispersions [28][29][30][31]. Compared with LS(0) gel, the storage modulus (G') of LS(0.20) gel was found to be about 8.2 times higher.…”
Section: Rheological Properties Of Ls Gelssupporting
confidence: 89%
“…Similar behavior was observed for oleogel-like dispersions containing ethylene vinyl acetate copolymer (EVA) and higholeic sunflower (HOSO) vegetable oil [11]. The reason is that oleogels with lower viscosity and viscoelastic moduli are easier to generate a protective lubricating film in comparison with oleogels with higher viscosity and viscoelastic moduli [10]. Thanks to the good friction reduction and anti-wear (AW) properties, oxidation inhibition, and low toxicity, intensive research has been done on using borates as high-performance and eco-friendly lubricant additives [12][13][14], and their results indicated that the good tribological performance of borate is ascribe to the boundary lubrication film formed by borate esters adsorbed on the sliding surfaces and tribochemical reaction between borate esters and steel surfaces [14].…”
Section: Introductionsupporting
confidence: 57%
“…However, there is room to improve the mechanical stability (rheological parameters) and tribological properties of lubricating grease simultaneously, as increasing the rheological properties of grease usually do not prevent friction and wear reduction. For instance, the lubricating grease based on nano-montmorillonite and castor oil with higher thickener agent (commercial organo-montmorillonite Cloisite 20A) achieved higher friction coefficient at different normal loads (10 N and 30 N) [10]. Similar behavior was observed for oleogel-like dispersions containing ethylene vinyl acetate copolymer (EVA) and higholeic sunflower (HOSO) vegetable oil [11].…”
Section: Introductionmentioning
confidence: 63%
“…Since the double bonds in the fatty acid chains in vegetable oils quickly react with oxygen, and a high content of double bonds is found in vegetable oils, such as sunflower, soybean, olive, linseed, and palm. The development of oleogels to formulate eco-friendly semi-solid lubricants based on nanoclay such as sepiolite and organo-montmorillonite with castor and soybean oils have been reported [ 25 , 26 , 27 ]. Particularly, the effect of the thickener concentration on the rheological, chemical, thermal and tribological properties, of these systems have been studied.…”
Section: Introductionmentioning
confidence: 99%